Практика радиографического контроля: учебное пособие - Кулешов В. К. Валерий Константинович; Сертаков Ю. И. Юрий Иванович; Ефимов П. В. Павел Васильевич; Шумихин В. Ф. Вячеслав Федорович (Томск, Изд-во ТПУ, 2009)
Заглавие с титульного экрана